Arthropofauna diversity along an andean altitudinal gradient of Peru - Olano-Panchano, Paola Esthefanie (2025)
The study of arthropod diversity in altitudinal gradients provides information on the state of an ecosystem affected by various environmental impacts. In the Andes of Peru, the Twin Lagoons are located in the province of Huarochirí, district of Matucana and annex of Marachanca, Lima, Peru at 3500 meters above sea level. The objective of the present investigation was to evaluate the diversity of arthropofauna in five points along an Andean altitudinal gradient of Peru between 2500 to 3500 meters above sea level, Huarochiri, Perú, between August and September 2022. The four types Sampling methods for collecting arthropod fauna were: manual type, entomological net, yellow traps (pantraps) and pitfall (necrotrap) during four biweekly field trips. The total number of morphospecies found was 32 with 165 individuals, the Cicadellinae sp2 morphotype was the most abundant, followed by Cicadellinae sp3. The trophic guilds presented the following sequence of importance from highest to lowest: predator (43.75%) > phytophagous (25%) > pollinator (21.86%) > omnivore (3.13%) = detritivore (3.13%) = parasitoid (3.13%). The point of highest altitude presented the highest values for four alpha diversity indices: number of individuals of the arthropofauna, Shannon-Wienner (H`), richness of Margalef, Chao-1 and Chao-2 in comparison to the other four points of sampling. The altitudinal gradient towards the Twin Lagoons of Orcococha was only found positively associated with the Chao-1 and Chao-2 indices, which shows a greater estimated abundance at 3500 meters above sea level. The beta diversity indices of qualitative (Jaccard) and quantitative (Bray-Curtis) similarity show an absence of a pattern with the altitudinal gradient between the arthropofauna sampling points.